Integration of clean and healthy living behavior and home environment: A holistic approach to controlling pulmonary tuberculosis - As, Asrar; Sabriadi, Ririn; Mukty, Marifat Istiqa; Sanas, Nurhidayah Tiasya (EcoVision: Journal of Environmental Solutions, 2025)
Background: Pulmonary tuberculosis (TB) is a contagious infectious disease that remains a major public health problem, particularly in developing countries such as Indonesia. One of the contributing factors to the high transmission rate of pulmonary TB is the low implementation of Clean and Healthy Living Behavior, as well as poor household environmental conditions that do not meet health standards. This study aimed to determine the correlation between clean and healthy living behavior and the condition of the home environment among pulmonary TB patients at Puskesmas Gattareng, Bulukumba Regency. Methods: This research employed a descriptive analytic design with a cross-sectional approach, involving 38 respondents selected through simple random sampling from a total population of 42 patients. Data were collected using a clean and healthy living behavior questionnaire adapted from Alpul Laely and a healthy house assessment instrument based on criteria from the Indonesian Ministry of Health. Data were analyzed using univariate and bivariate analysis with the Spearman Rho test at a significance level of α = 0.05. Findings: The findings showed that most TB patients had a moderate level of clean and healthy living behavior (39.2%) and lived in unhealthy homes (57.9%). The statistical test revealed a strong correlation between clean and healthy living behavior and the condition of the home environment among TB patients (ρ = 0.01; r = 0.772). Conclusion: There is a significant relationship between clean and healthy living behavior and the condition of the home environment of pulmonary TB patients. Improving clean and healthy living behavior and housing conditions plays a crucial role in TB control efforts within the community. Novelty/Originality of this article: The novelty of this study lies in linking clean and healthy living behavior with home environment conditions among pulmonary TB patients.